Content and Structure of Competitive Activities of Young Basketball Players Aged 13-14 - Viktor Koryahin; Halyna Hrebinka (OVS LLC, 2023)
The study purpose was to determine the technical-and-tactical indicators of young basketball players aged 13-14 in the process of competitions and to develop recommendations for assessing the competitive activities of young basketball players. Materials and methods. The study used the method of pedagogical observations during competitions with recording in a specially developed protocol the following indicators of competitive activity of young basketball players: throws to the basket in motion, two- and three-point throws, free throws, quick breakthrough, positional attack, struggle for rebounding the ball, interception of the ball, "goal assists", technical errors, and other losses of the ball. Results. As shown by the results of studies of such a technical indicator as throwing the ball into the basket in motion, young basketball players aged 13-14 have the highest accuracy in hitting the basket in this technique of the game - 49.1%. Moreover, the hit percentage (51.6) is higher in the first half of the game than in the second half (46.6) with a high significance level of the difference (p>0.99). A similar situation is observed when making two- and three-point shots from the distance. Studies of the effectiveness of free throws have shown that, on average, basketball players aged 13-14 make 14.1 free throws, of which 7.1 hit, which is 52.2 %. Studies have shown that the number of quick breakouts averages 8.45 per game (5.18 in the first half and 3.27 in the second half). The number of possessions of the ball in the fight for the rebound on own backboard is 14.9 times, and on the opponent's backboard - 13.36. The average number of "goal assists" per game is 4.36, ball interceptions - 8.18, technical errors - 15, and other ball losses - 9.54. Conclusions. Studies of technical-and-tactical indicators of young basketball players during competitions have shown that their role is underestimated in the practice of training young basketball players. The training programs for basic training groups (aged 13-14) shall include in full all technical-and-tactical indicators, and especially throws in motion from under the backboard, two- and three-point shots, "goal assists", free throws, ball losses, interceptions, block shots, struggle for rebound, indicators in a quick breakthrough and in a positional attack, the number of points conceded, etc. It should be noted that there is a higher number of technical-and-tactical indicators in the first half of the game, compared to the second half, with a high significance level of the difference between the indicators. This indicates the growing fatigue of young basketball players and the need to find ways to improve the system of training speed endurance and throwing techniques in a state of fatigue.